Design Of A Lowpower 5-Gb/S Fully Balanced And Differential Output Transimpedance Amplifier - Shammugasamy, Balasubramaniam (2013)
This thesis presents the design of a Transimpedance Amplifier (TIA) for the HDMI interface operating at data rate of 5-Gb/s. The TIA design employs a fully balanced and differential output configuration from a single 1.8-V power supply for better noise rejection to achieve good input optical sensitivity. This design is implemented using 0.18-mm Complementary Metal-Oxide-Semiconductor (CMOS) technology as it provides higher bandwidth due to technology scaling. The TIA uses the Regulated Cascode (RGC) circuit as an input block for photodiode capacitance isolation and shunt feedback stage for differential swing amplification. To meet the requirement for 4- GHz bandwidth in the TIA design, an active inductor and capacitive de-generation techniques have been implemented in the existing RGC and shunt feedback architecture, respectively. These two implementations extend the bandwidth without using a large amount of Direct-Current (DC) current to drive output capacitive load. The TIA design also employs the Common-Mode Feedback (CMFB) and DC offset cancellation circuit to form a fully balanced and differential output configuration, specifically for the improvement of common mode noise rejection and better input sensitivity for HDMI optical interface.